Impact of patient choice and hospital competition on patient outcomes after prostate cancer surgery: A national population‐based study. Issue 11 (1st February 2019) - Aggarwal, Ajay K.; Sujenthiran, Arunan; Lewis, Daniel; Walker, Kate; Cathcart, Paul; Clarke, Noel; Sullivan, Richard; van der Meulen, Jan H.
Abstract : Background: Policies that encourage patient choice and hospital competition have been introduced across several countries with the purpose of improving the quality of health care services. The objective of the current national cohort study was to analyze the correlation between choice and competition on outcomes after cancer surgery using prostate cancer as a case study. Methods: The analyses included all men who underwent prostate cancer surgery in the United Kingdom between 2008 and 2011 (n = 12, 925). Multilevel logistic regression was used to assess the effect of a radical prostatectomy center being located in a competitive environment (based on the number of centers within a threshold distance) and being a successful competitor (based on the ability to attract patients from other hospitals) on 3 patient‐level outcomes: postoperative length of hospital stay >3 days, 30‐day emergency readmissions, and 2‐year urinary complications. Results: With adjustment for patient characteristics, men who underwent surgery in centers located in a stronger competitive environment were less likely to have a 30‐day emergency readmission, irrespective of the type or volume of procedures performed at each center (odds ratio, 0.46; 95% confidence interval, 0.36‐0.60; P = .005). Men who received treatment at centers that were successful competitors were less likely to have a length of hospital stay >3 days (odds ratio, 0.49; 95% confidence interval, 0.25‐0.94; P = .02). Conclusions: The current results suggest for the first time that hospital competition improves short‐term outcomes after prostate cancer surgery. Further evaluation of the potential role of patient choice and hospital competition is required to inform health service design in contrast to the role of top‐down–driven approaches, which have focused on centralization of services. Abstract : Hospital competition improves short‐term outcomes after prostate cancer surgery. Further evaluation of the potential role of patient choice and hospital competition is required to inform health service design.